Performance-Oriented Grants for local Self-Government Units - the Added Value of Performance-Based Budget - Kańduła, Sławomira (Studia Oeconomica Posnaniensia, 2013)
The award of grants as a source of revenue for local and regional self-government units are criticized because they limit their financial autonomy, and do not create adequate incentives to either increase their fiscal effort, improve the efficiency of public expenditure or increase accountability. The literature proposes the co-financing of the activities of local government units in the form of grants focused on performance/results. These types of grant are called performance-oriented grants. A local government unit will receive these grants if it achieves specifi c results. In contrast to traditionally awarded grants, the local and regional self-government unit has the freedom to defi ne how to perform the task and get the required results. Local government units being evaluated on results, not on total spending, is reminiscent of the concept of performance-based budgeting. The coincidence between this budget and such grants is the basis for the thesis that the dissemination of performance-based budgeting in the public finance sector in Poland will be an incentive to the rationalization of grants for local and regional self-government units. If this happens, the implementation of performance-oriented grants will provide added value to performance-based budgeting.